2019
DOI: 10.1111/jgh.14928
|View full text |Cite
|
Sign up to set email alerts
|

Infection, antibiotic exposure, and risk of celiac disease: A systematic review and meta‐analysis

Abstract: Background and Aim There is evidence of a relationship between infection (and the associated antibiotic exposure) and the risk of celiac disease (CD). This study performed a meta‐analysis to investigate this relationship. Methods To identify relevant studies, we conducted systematic searches of the PubMed, Embase, and Cochrane databases for articles published up to April 2019. Random effects models were used to determine overall pooled estimates and 95% confidence intervals (CIs). Results The meta‐analysis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Antibiotics are provided to approximately 25% of pregnant women and account for nearly 80% of all medications prescribed during pregnancy. 158 , 159 Evidence supporting an association between early antibiotic exposure and the risk of allergy/atopy, 160 obesity, 161 diabetes, 162 and celiac disease, 163 and concerns regarding antibiotic resistance, 164 highlight the need for management guidelines regarding the requirement, dose, and duration of perinatal antibiotics considering the risk of altering maternal and offspring intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are provided to approximately 25% of pregnant women and account for nearly 80% of all medications prescribed during pregnancy. 158 , 159 Evidence supporting an association between early antibiotic exposure and the risk of allergy/atopy, 160 obesity, 161 diabetes, 162 and celiac disease, 163 and concerns regarding antibiotic resistance, 164 highlight the need for management guidelines regarding the requirement, dose, and duration of perinatal antibiotics considering the risk of altering maternal and offspring intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…VEO-IBD is considered a different entity from later-onset IBD, 44 since genetics play a far more important aetiological role than microbial dysbiosis. 45 This may explain the lack of an association with early life antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…TEDDY group of investigators has recently reported that the childhood gastrointestinal infection, not respiratory infections, is associated with increased risk of coeliac autoimmunity in genetically susceptible individuals (hazard ratio 1.33) 155 . Furthermore, a systemic review and meta‐analysis including 19 observational studies has shown that any infection in childhood is associated with a 37% increase in the odds of developing CD, particularly among those requiring hospitalisation 156 …”
Section: Risk Factors For CDmentioning
confidence: 99%